Establishment of a Sink Gallery to Investigate Growth of Carbapenemase-Producing Klebsiella pneumoniae and Biofilms in P-Traps. (October 2020) - Ganim, Christine; Mazher, Mustafa; Breaker, Erin
Abstract : Background: Hand-hygiene sink drains in healthcare facilities may provide an environment for the survival and dissemination of various multidrug-resistant organisms (MDROs), including carbapenemase-producing Klebsiella pneumoniae (CPKP). We developed a sink model system to establish and test native drinking water biofilms containing CPKP in the p-traps of hand-hygiene sink drains. Methods: A handwashing sink gallery was designed to consist of 6-wall mounted stainless-steel sink basins connected to the same municipal water line. Each sink's plumbing included a chrome-plated brass p-trap. Healthcare facility conditions were simulated to include handwashing events with the addition of hand-soap and municipal water 4 per day, and nutritional shake (simulating liquid waste) 1 per day. Resultant biofilms in the p-traps of each sink were harvested after 28 days for community analysis. Microbial community analyses were performed on selected biofilm samples using 16S rRNA sequencing of the V4 hypervariable region of genomic DNA. Another experiment evaluated 28-day p-trap biofilm inoculated with CPKP CAV1016 (10 mL 7.010E 7 CFU/mL) and was assessed over 14 days. Heterotrophic plate counts (HPCs) were determined on R2A medium (7 days of incubation at 25C). CPKP was quantified on mEndo selective medium (48 hours of incubation at 36C). Results: Biofilms developed in all p-traps, but biofilm HPC (5.78 mean log CFU/cm 2, range 4.35–7.16) and community diversity (15–20 genera per p-trap) varied with sink position. Community analysis showed similarities in bacterial community composition and diversity between sinks 1 and 2, and between sinks 3, 5 and 6, but with differences between the 2 groups. The most abundant family in sinks 3, 5, and 6 was Erythrobacteriaceae (76%, 78%, and 55% of the total reads, respectively), whereas sinks 1 and 2 were dominated by Sphingomonadaceae (63% and 36%) and Methylobacteriaceae (19% and 55%). Also, 16S sequencing revealed the presence of potential opportunistic pathogens in the biofilms, including reads attributed to Pseudomonas and Acinetobacter . CPKP CAV1016 inoculated into 28-day p-trap biofilms colonized and persisted in all 6 sinks for 12 days after inoculation. Conclusions: Despite all 6 sinks sharing an incoming water line, soap, and carbon and energy source, there was a significant variation in the bacterial community composition observed between the sinks. CPKP can colonize and persist in the p-trap biofilms; however, additional work is needed to achieve a reproducible model system. Once this is achieved, the sink gallery will be used to investigate interventions to mitigate colonization or persistence of CPKP in p-trap biofilms. Funding: None Disclosures: None